2020
DOI: 10.1007/s00592-020-01614-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 lockdown on flash and real-time glucose sensor users with type 1 diabetes in England

Abstract: Aims People with type 1 diabetes (T1D) face the daily task of implementing self-management strategies to achieve their glycaemic goals. The UK COVID-19 lockdown has had an impact on day-to-day behaviour, which may affect diabetes self-management and outcomes. We assessed whether sensor-based outcomes pre- and during lockdown periods were different in a cohort of glucose sensor users with T1D. Methods Data were collected from Freestyle Libre (FSL) or Dexcom G6 sensor users who remotely shared their data with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 20 publications
2
28
0
Order By: Relevance
“…Overall, we analyzed n = 2881 T1D patients. Of n = 25 T1D studies, n = 18 (72%) showed clear, significant improvements in glycemic control [ 14 31 ], n = 4 (16%) showed stability (no changes) [ 32 35 ] and n = 3 (12%) deteriorations [ 36 38 ]. In n = 10 studies, the patients received CGM treatment, in n = 5 studies FGM, in n = 2 studies HCL, in n = 1 study SAP, in n = 5 studies mixed types of technology such as MDI, CSII, CGM, FGM, insulin pump, and in n = 2 papers no digital treatments were described.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, we analyzed n = 2881 T1D patients. Of n = 25 T1D studies, n = 18 (72%) showed clear, significant improvements in glycemic control [ 14 31 ], n = 4 (16%) showed stability (no changes) [ 32 35 ] and n = 3 (12%) deteriorations [ 36 38 ]. In n = 10 studies, the patients received CGM treatment, in n = 5 studies FGM, in n = 2 studies HCL, in n = 1 study SAP, in n = 5 studies mixed types of technology such as MDI, CSII, CGM, FGM, insulin pump, and in n = 2 papers no digital treatments were described.…”
Section: Resultsmentioning
confidence: 99%
“…A study among patients with well-controlled type 2 diabetes mellitus showed worse glucose control during lockdown, which was worse among patients with higher fasting triglyceride levels pre-lockdown [ 30 ]. On the contrary, some studies found better glycaemic control in patients with type 1 diabetes mellitus during lockdown, which could be due to having more time for self-management during lockdown, at least in the short term [ 29 , 31 , 32 , 33 ] or due to reduced work-related stress [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…For T1DM, there are many reports of improved glycaemic control. Improvement has been reported in many countries, such as India [ 9 ], the UK [ 10 , 11 ], and Spain [ 12 14 ]. In contrast, a report of 50 patients in Rome, Italy, indicated that glycaemic control was markedly worsened during the lockdown [ 15 ], and a study of 52 patients in Rohtak, an industrial city in Northern India, reported an increase from 8.8 ± 1.3% before the lockdown to 10.0 ± 1.5% after the lockdown [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Reports available to date show results that vary among regions and subjects [5][6][7][8][9][10][11][12][13][14][15][16]. There is, however, still no report on the actual conditions of changes in lifestyle and treatment status of patients with diabetes before and after the declaration.…”
Section: Introductionmentioning
confidence: 99%